Pharmacokinetics, biodistribution and toxicology following intravenous and oral administration of DSM‐RX78 and EFB‐1, two new 2‐(2‐fluorobenzamido)benzoate‐based PDE4 inhibitors, to rats. (2nd November 2012) - Fang, Jia‐You; Liu, Yi‐Ting; Huang, Yaw‐Bin; Pan, Tai‐Long; Wang, Han‐Hsiang; Hsieh, Pei‐Wen
Abstract: Objectives: The aim of this study was to determine the pharmacokinetic profile, biodistribution and toxicity of ethyl 2‐(2‐fluorobenzamido)benzoate (EFB‐1) and methyl 2‐(2‐fluorobenzamido)benzoate (DSM‐RX 78), two phosphodiesterase IV inhibitors, which potently attenuate haemorrhagic shock‐induced lung injury in rat. Methods: Quantification of DSM‐RX78, EFB‐1 and 2‐(2‐fluorobenzamido)benzoate (SMP‐3) in plasma was carried out by HPLC. Furthermore, the pharmacokinetics and biodistribution of intravenously (1.0 and 3.0 mg/kg) and orally (40.0 mg/kg) administered DSM‐RX78, EFB‐1, and SMP‐3 were determined in Sprague–Dawley rats. Toxicity and histological analyses were also evaluated herein. Key findings: A liquid chromatography method has been developed for the quanification of EFB‐1, DSM‐RX78 and SMP‐3 in rat plasma. The method was sensitive with good linearity ( r 2  = 0.9990) over a range of 1.56–0.0975 μg/ml. The mean kinetic parameters of DSM‐RX 78 and EFB‐1 following intravenous administration were as follows: elimination half‐life (t½) 8.98 and 8.77 min; clearance (Cl) 24.57 and 22.31 ml/min/kg; AUC0‐ ∞ 41.76 and 48.03 min mg/l. Conclusions: The pharmacokinetics, toxicity and biodistribution of DSM‐RX78 and EFB‐1 were determined for the first time. The results showed that the pharmacokinetic profiles of DSM‐RX78 and EFB‐1 were similar, and that EFB‐1 had a better safety profile than DSM‐RX78. Therefore, EFB‐1 was suitable as a lead compound for the development of new agents in the treatment of neutrophilic inflammatory diseases.